Justified slander - صافي مناف (Latakia University Journal - Economic and Legal Sciences Series, 2025)
In this research, I discussed the crime of defamation stipulated in the Syrian penal legislation as a crime of insult. I dealt with the research topic in two sections, the first of which was about the nature of the crime of defamation by defining it, its pillars, its forms, and the nature of the violated right. As for the second, I talked about the two cases in which the legislator explicitly gave a reason to justify the perpetrator of the crime of defamation, and about other cases that were not explicitly stipulated within the framework of the texts that dealt with this crime, but are in fact a consecration of the principle of using the right stipulated in Article /182/ of the Penal Code. Finally, I reached a set of results in addition to a set of recommendations that contribute to enriching the research.